The Bastille : A History of a Symbol of Despotism and Freedom - Lüsebrink, Hans-Jürgen; Reichardt, Rolf (Book collections on Project MUSE., 1997)
This book is both an analysis of the Bastille as cultural paradigm and a case study on the history of French political culture. It examines in particular the storming and subsequent fall of the Bastille in Paris on July 14, 1789 and how it came to represent the cornerstone of the French Revolution, becoming a symbol of the repression of the Old Regime. Lüsebrink and Reichardt use this semiotic reading of the Bastille to reveal how historical symbols are generated; what these symbols' functions are in the collective memory of societies; and how they are used by social, political, and ideol.